Business plan of Bếp nhà Gà - An authentic Vietnamese food taste. - Hoang, Nguyen Xuan Mi; Kubíček, Aleš; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis aims to develop a business plan for opening a Southern Vietnamese-flavored restaurant in Prague and the feasibility of this project. The thesis is divided into two parts: theoretical and practical. The theoretical part describes definitions of business types, methods, and related tools for developing a business plan. Additionally, it dives into the operational elements such as operating a business in the market, studying the characteristics, processes, and methods in business evaluation. The practical part, based on the theoretical part, analyses the basic characteristics of the business, reviews the development of the business by analyzing strategical and financial aspects. The thesis will show whether this project can be implemented or not.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses